Neoliberal schooling: Where kids clock in and dreams clock out - Kuyurtar, Dilan; Korumaz, Mithat (WILEY, 2026)
This study critically examines the school and work experiences of Vocational Training Centre (VTC) students in T & uuml;rkiye, situating these experiences within debates on neoliberal rationality, vocational education policies, class reproduction and child labour. Drawing on Man van Manen's hermeneutic phenomenological approach, the research analyses 14 dialogue-based interviews with students to explore how working-class identities and subjectivities are constructed through the intersection of schooling and early labour. Van Manen's existential themes of lived space, lived body, lived time and lived human relations guided the interpretive analysis, allowing for a nuanced understanding of students' experiences within socio-cultural, economic and institutional contexts. Findings reveal four central themes. First, 'Negotiating Vocational Belonging' highlights the internalization of vocational identities alongside early labour participation, often under exploitative conditions. Second, 'Fragmented Trajectories' emphasizes educational inequalities and institutional marginalization shaping discontinuous career paths. Third, 'Structural Compulsions' demonstrates that vocational education often reflects socioeconomic necessities rather than choice, reinforcing class hierarchies through a 'vocational habitus'. Finally, 'Hope Amid Precarity' illustrates the tension between students' aspirations and the risks of early labour exploitation. By foregrounding the lived experiences of VTC students, this research contributes to international debates on vocational education, revealing how neoliberal policies and structural inequalities intersect to shape youth subjectivities. The study highlights the critical need for reforms that prioritize students' rights, agency and holistic development, offering insights for policy and practice in contexts of labour-oriented vocational education while emphasizing the ethical imperative to protect young learners.
Keywords: child labour; class reproduction; neoliberal rationality; vocational education; HERMENEUTIC PHENOMENOLOGY; VOCATIONAL-EDUCATION; LABOR; CONTRADICTION; REPRODUCTION; EXPERIENCES; Education & Educational Research